MECHANISM OF ACTION AND TYPES OF MEDIATORS THAT OCCUR IN INFLAMMATION. - Ergashov Bekhruzjon Komilovich (TADQIQOTLAR.UZ, 2024)
Abstract: Identifying the etiology of inflammation, the types of mediators that occur during inflammation, the mechanism of the effect of mediators on the body